NATIONAL IDENTITY OF CONTEMPORARY ART AND DESIGN IN A GLOBALIZED SOCIETY - Yurchenko, Ihor; Kravchenko, Mariia; Kharitontsev, Kyrylo; Penchuk, Oleksandra; Rozputenko, Taras (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The issue of preserving national identity in the context of globalization and digitalization is becoming particularly relevant, in particular for peoples who are under the influence of more powerful states in various fields. The spread of digital technologies contributes to the formation of a global culture, which often displaces local cultural narratives. At the same time, there is a growing interest in preserving cultural diversity and local identity. The interaction of these opposing trends creates a complex context in which cultural practices are transforming and new strategies for preserving and reproducing national identity are being developed. The purpose of this study is to predict the future of national identity based on trends observed in contemporary art, given its ability to represent nationally characteristic artistic images and symbols. The study uses an interdisciplinary approach that combines a critical analysis of scholarly works on national identity with a cultural analysis of digital artifacts in the fields of music, fine arts, and design. The study reveals the diversity of forms of representation of national identity in digital art, particularly in music, visual arts, and design. These possibilities give grounds for an optimistic forecast of the future of national identity, provided that there is a significant public interest in folk culture and appropriate support for art at the state level or from patronage communities.